2018
DOI: 10.1161/circep.118.006576
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ablation Index-Guided Ablation Results in High Rates of Durable Pulmonary Vein Isolation and Freedom From Arrhythmia in Persistent Atrial Fibrillation Patients

Abstract: Background Catheter ablation for persistent atrial fibrillation (AF) is associated with less favorable outcomes than for paroxysmal AF. Substrate modification is often added to pulmonary vein isolation (PVI) to try to improve success rates. Recent studies have shown improved clinical outcomes with use of regional ablation index (AI) targets for PVI. We hypothesized that prospective use of AI-guided PVI in persistent AF patients would result in a low rate of PV reconnection at repeat electrophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
271
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(290 citation statements)
references
References 23 publications
16
271
3
Order By: Relevance
“…Interestingly, the first clinical study utilizing AI‐guided PVI demonstrated that insufficient AI values predicted PV reconnection, and a minimum AI value of 370 (posterior wall) and 480 (anterior wall) was associated with durable lesions . Recent clinical studies targeting AI values of 550 (anterior wall) and 400 (posterior wall) were associated with high single‐procedure success rate and low rate of PV reconnection …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the first clinical study utilizing AI‐guided PVI demonstrated that insufficient AI values predicted PV reconnection, and a minimum AI value of 370 (posterior wall) and 480 (anterior wall) was associated with durable lesions . Recent clinical studies targeting AI values of 550 (anterior wall) and 400 (posterior wall) were associated with high single‐procedure success rate and low rate of PV reconnection …”
Section: Discussionmentioning
confidence: 99%
“…The Visitag (CARTO3; Biosense Webster) settings included: ILD ≤6 mm, minimum force 3 g, force‐over‐time 30%, minimum time 3 seconds, maximal range 2 mm, and lesion tag size 3 mm. According to LA location different target AI values were defined (AI 550 for anterior, and AI 400 for posterior) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the ablation index (AI) was proposed as a similar quantitative ablation lesion marker by including CF, RF application time, and RF power in a weighted formula. AI was reported to be useful to create durable ablation lesion and to minimize AF recurrence after ablation . However, these studies did not evaluate the impact of RF application power on AI‐guided CPVI.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have demonstrated that when the achieved lesion AI value is ≥370 for the posterior/floor segments and ≥480 for the anterior/roof segments, no PV reconnections were seen at 2 months . This protocol has been shown to result in high levels of first‐pass PVI and relative fast procedures using standard power settings in two single center pilot studies …”
mentioning
confidence: 88%